Alternative Methods Of Handling Three Unsignalized Intersections Using Traffic Management On Ujungrusi Highway II Adiwerna Sub-District Tegal District - Yusuf, Muhamad; Salsabilla, Nadya Shafira; Hermawan, Okky Hendra; Weimintoro, W; Pratama, Hasemi Rafsanjani (JACEE (Journal of Advanced Civil and Environmental Engineering), 2025)
Abstract: Ujungrusi Highway II is an alternative route that connects Tegal regency and city, passed by various vehicles every day. The three intersections on this road have different sizes and elevations, but lack signs, road markings, and clear dividing lines, confusing road users. The presence of restaurants, stalls, and indiscriminate parking further worsens the smooth flow of traffic, exacerbated by the absence of traffic lights that trigger congestion, especially during peak hours. This study aims to analyze side barriers, evaluate intersection performance, and determine the level of congestion using the MKJI (1997) method to design solutions. Data was collected through direct observation, including traffic flow, intersection conditions, and environmental factors. The results showed that the highest volume occurred on Monday morning (06.00-08.00 WIB), with medium class side obstacles (M), an intersection capacity of 2,294.52 pcu/h, and a Degree of Saturation (DS) of 1.185. With LoS category D (25.1-40 seconds/pcu), this intersection is classified as poor, so strategic steps are needed to overcome congestion.Keywords: MKJI 1997; Triple intersection analysis; Unsignalized intersection.